A LITERATURE REVIEW: FACTORS INFLUENCING THE INCIDENCE OF ANEMIA IN FARMERS IN THE WORLD - Radi, Radi; Rejeki, Dwi Sarwani Sri; Octaviana, Devi (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
Background: Studies on anemia have so far focused more on the incidence of anemia in pregnant women and adolescent girls even though farmers are one of the vulnerable groups suffering from anemia. The incidence of anemia in farmers has not been well documented, and there is still very limited research related to the determinants of anemia incidence in farmers. Objective: The study aim to know risk factor anemia in the farmers around the world Method: This study used the literature review method by collecting journals from google scholar, PubMed, and cienceDirect. Data collection using Anaemi A keywords Anemia AND farmers AND risk faktor. The results of the livelihood obtained a total of 4,959 articles which were then carefully selected so that 8 of the most relevant articles were obtained for article review. Result: The results showed that there are three main faktors that cause the incidence of anemia in farmers, namely individual factors, environmental factors, and sociodemographic factors. Conclusion: Risk factor of anemia in the farmers is individual factors, environmental factors, and sociodemographic factors Keyword: Anemia, Farmers, Risk Factor